2000
DOI: 10.1093/oxfordjournals.aje.a010185
|View full text |Cite
|
Sign up to set email alerts
|

Does Arsenic Exposure Increase the Risk for Circulatory Disease?

Abstract: Studies of residents in communities with high endemic concentrations of arsenic in drinking water suggest a deleterious effect on the circulatory system; however, studies among workers with high occupational exposures generally have shown either no or weak associations. This discrepancy could be a result of the healthy worker effect, including the healthy hire component and the healthy worker survivor effect (HWSE). Therefore, the authors conducted analyses of arsenic exposure in relation to circulatory diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 27 publications
1
43
0
1
Order By: Relevance
“…Arrighi & Hertz-Picciotto (20) found that adjustment for the healthy worker survivor effect failed with several methods to change the shape of the exposure-response curve for lung cancer and arsenic exposure, and they concluded that it was unlikely to explain fully the nonlinear exposure-response relationship observed in these studies. In contrast, control for confounding by the healthy worker survivor effect using lagging or controlling for employment status did appear to change the exposure response from a flat to a positive slope in an analysis of cardiovascular disease and arsenic exposure (21).…”
Section: Healthy Worker Survivor Effectmentioning
confidence: 70%
“…Arrighi & Hertz-Picciotto (20) found that adjustment for the healthy worker survivor effect failed with several methods to change the shape of the exposure-response curve for lung cancer and arsenic exposure, and they concluded that it was unlikely to explain fully the nonlinear exposure-response relationship observed in these studies. In contrast, control for confounding by the healthy worker survivor effect using lagging or controlling for employment status did appear to change the exposure response from a flat to a positive slope in an analysis of cardiovascular disease and arsenic exposure (21).…”
Section: Healthy Worker Survivor Effectmentioning
confidence: 70%
“…Exposure by food:It has been found that rice is particularly susceptible to accumulation of arsenic from soil [27].Rice grown in U.S.has an average 260ppb of arsenic, according to a study, but U.S. arsenic remains far below WHO recommended limits [28].China has set a standard for arsenic limits in food(15ppb) [29] as levels in rice exceeds those in water [30].Arsenic is an ubiquitous element present in American drinking water [31].In the United States levels of arsenic that are above natural levels, but still well below danger level set in Federal safety standards, have been detected in commercially grown chickens [32].The source of arsenic appears to be the food additive roxarsone and nitrasone,which are used to control the parasitic infection coccidiosis as well to increase weight and skin coloring [33].High levels of inorganic arsenic were reportedly found in 83 California wines in 2015 [34].Subacute arsenic poisoning caused by ingestion of an arsenic contaminated beer is associated with cardiomyopathy and cardiac failure [35].…”
Section: Contributory Factors Inarsenic Poisoningmentioning
confidence: 99%
“…In contrast, the lung cancer risk of smokers without arsenic in their water was about six times that of non-smokers. This, along with the vascular effects of both arsenic and smoking (Tseng et al, 1996;Engel et al, 1994;Chen et al, 1996Chen et al, , 1988Hertz-Picciotto et al, 2000) might suggest that those who have been exposed to arsenic in water should be advised not to smoke. However, since smoking kills nearly one in two persons without arsenic in their water, it hardly seems pertinent to point out that smokers who have arsenic in their water have even greater risks.…”
Section: Smokingmentioning
confidence: 99%